About some parallels in Anna Russ’s poems for children and adults - Алешка, Татьяна (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2012)
This article is devoted to the features of Anna Russ's poems for children and their compliance to poetics of this genre and parallels with her poems for adults.